Parenting Culture on The Role of Father in Prevention of Stunting in Toddler - Luluk Fauziyah Januarti; Ariska Putri Hidayathillah (Babali Nursing Research, 2020)
Introduction: Prevention of stunting in toddler is one of the roles of fathers in protecting against danger. However, most fathers still play a passive role in this regard. Madura culture sees the role of father only as head of families and breadwinner in the family. The purpose of the research is to analyze the effect of parenting culture on the role of fathers in prevention of stunting in toddler. Methods: The research design is observational with cross sectional approach. Exogenous variables are parenting culture while the endogenous variables are the role of fathers and prevention of stunting in toddler. The research population is 230 fathers with a sample of 132 fathers using the cluster sampling method. The research instrument used is a research questionnaire. This research uses statistical test Binary Logistic Regression. Results: The results of the research with the Binary Logistic Regression test showed that the role of father significantly affected the prevention of stunting with the result of sig 0.001 <α 0.05. Parenting culture significantly influences the prevention of stunting in toddler with the result of sig 0.019 <α 0.05. This shows that the role of father will increase the prevention of stunting in toddler, parenting culture will increase the role of father and parenting culture will increase prevention of stunting in toddlers. Conclusion: Parenting culture is beneficial for father in increasing their roles in preventing stunting in toddlers and it is important for nurses to understand their culture before understanding transcultural nursing applied to society.